معايير اختيار نوع السفينة وطاقتها التحميلية السنوية - حوا رامي (Latakia University Journal -Engineering Sciences Series, 2019)
إن التنوع الكبير في أنواع السفن يضع أمام مالك السفينة سؤالاً معقداً مفاده: ما هو النوع الأنسب اقتناؤه ؟ وهذا سؤال مهم جداً قبل الإقدام على الشراء؛ لذلك عندما تقرر شركة بحرية أو فرد امتلاك وحدة بحرية تنجز مهمة معينة أو خدمة, يتحتم عليها القيام بما يسمى الدراسة التنفيذية، وهي دراسة اقتصادية فنية تبحث في التحقق الفني والتقني للسفينة وتكاليفها، وربح التشغيل الإجمالي الذي يتم الحصول عليه من الفرق بين الإيرادات المتوقعة ونفقات التشغيل المقدرة؛ إذ إنّ الهدف النهائي لتلك الدراسات هو الوصول لقرار رفض هذه الفرص الاستثمارية أو قبولها. وفي هذا البحث تم التركيز على الجانب المتعلق ببرامج التشغيل، والعوامل التي تحكم قرار اختيار النوع الأكثر ربحية من السفن التي سيتم امتلاكها وتشغيلها، كما تم حساب طاقة النقل للسفينة خلال فترات محددة ومقارنة النتائج. What is the most appropriate type of Vessels to be purchased? This question is likely to face any vessel owner, due to he enormous variety of Vessels. It is an extremely significant question to be dealt with prior to vessel-purchase. Thus, when a maritime Company or an individual decides to own a maritime unit that accomplishes a certain mission or provides a service, it will be inevitable to conduct what can be termed as (executive study), which is a techno-economic study, dealing with the vessel’s structural and technical reliability, its costs, and the net-profit of the whole operation, calculated in the light of the expected profits and estimated operation costs. The final objective of the afore-mentioned studies is, then, to reach a decision with regard to taking or leaving these investment opportunities. In this research focus will be on operation schemes along with the factors that control the decision of selecting the most profitable vessel-type to be owned or run. Besides, the vessel’s transporting capability during specific time duration has been measured and the results have been accordingly compared.